PERKUATAN LERENG DENGAN RUMPUT VETIVER PADA DAERAH LERENG DI KELURAHAN REWARANGGA SELATAN KECAMATAN ENDE TIMUR KABUPATEN ENDE - Veronika Miana Radja; Yohanes Laka Suku; Marselinus Y Nissanson; Mikael Wora; Thomas Aquino A. S (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Rewarangga Selatan Village is mostly located in hilly areas. The transfer of land use to settlements will of course disrupt the stability of the existing slopes. Therefore, education and assistance are needed in the form of training and technical guidance on proper slope management so that stability is maintained. The training in this service activity aims to: equip the community with knowledge about the potential for landslide-prone slopes, provide alternative efforts to mitigate community-based landslide disasters and make people aware of environmental sustainability in slope areas. The training was carried out using lecture, demonstration and direct mentoring methods. The lectures were used to convey the concepts of: (a) introduction to landslides, (b) geographic information on potential landslides in the South Rewarangga Village, and (c) community-based landslide disaster mitigation using vegetative methods. Furthermore, there was a demonstration by the service team as resource persons, namely by providing an example of planting vetiver grass for mitigation of landslides at the service location. The results of the implementation of service activities show that the success of the target number of training participants (100%), the achievement of the training objectives (80%), the achievement of the planned material targets (90%), and the ability of participants in mastering the material (75%).